MENJADIKAN AL-QUR’AN SEBAGAI JIMAT: STUDI KRITIK HADIS - Abdurrahman Saleh Abdurrahman Saleh; Fishawar Fathan Madany Fishawar Fathan Madany; Muawiyah Ali Musri Muawiyah Ali Musri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
Talismans are things attached to children that are used to ward off reinforcements. Talismans containing verses of the Koran have differences of opinion among scholars, some of them allow it and some of them prohibit it with their own arguments. Hadith criticism is an attempt to assess the sanad and matan of hadith with the aim of recognizing the weaknesses and strengths of the sanad and establishing the truth and falsity of the matan. Researchers are interested in identifying and analyzing the hadiths that are used as arguments of the permissibility of wearing amulets from the Qur'an, namely the hadiths of 'Aisyah and Anas, the actions of Abdullah bin ‘Amr and the words of Aisyah. The purpose of this study is to collect hadiths and analyze the sanad and matan of each hadith that allows this. This research uses a qualitative approach with the type of hadith criticism research. The method used is the takhrij method or tracing the existence of hadiths and the naqd method or criticism of the structure of hadiths. It can be concluded that those are weak narrations except the words of Aisyah. In the history of Abdullah bin ‘Amr there is 'an'anah Muhammad bin Ishaq who is denounced as mudallis narrator and in the hadith of 'Aisyah and Anas there is a narrator named Sulaiman bin Abi Karimah who is denounced as munkar narrator and some of the narrators are unknowns.